Porous rubber cryogels: effect of the gel preparation temperature - TUNCABOYLU, DENIZ CEYLAN; Oztoprak, Zeynep; Hekimoglu, Tugce; Karakutuk, Ilknur; Tuncaboylu, Deniz C.; Okay, Oğuz (My University, 2014)
This paper examines the effect of the gel preparation temperature (T (prep)) on the physical properties of the rubber-based macroporous organogels prepared by solution crosslinking in benzene at subzero temperatures. Cis-polybutadiene (CBR) and styrene-butadiene rubber (SBR) were used as the rubber components, while sulfur monochloride (S2Cl2) was the crosslinker in the gel preparation. It was shown that T (prep) is an extremely important parameter to adjust the porous structure and thus, the cryogel properties. The networks formed by CBR and SBR showed an aligned porous structure with an exception of honey-comb structured porous SBR cryogels prepared at -2 A degrees C. 10(1)- to 10(2)-mu m sized regular pores of the networks caused by the benzene crystals act as a template during gelation, separated by 10-20 mu m pore walls in thickness. They exhibit fast swelling and deswelling properties as well as reversible swelling-deswelling cycles in toluene and methanol, respectively. The ability of the organogels for the removal of petroleum products from aqueous solutions was also demonstrated using diesel and crude oil as model pollutants. In addition, the reusability of the organogels and their continuous sorption capacities were checked by repeated sorption-squeezing cycles. All the tests showed that the aligned porous organogels are suitable materials for the oil spill cleanup procedures.